Empowering Teachers and Students to Cope with the Stress of Online Teaching and Learning: Findings from a Pilot Project on Psychosocial Support in the Language and Translation Classroom - Kitanovska-Kimovska Sonja, Katarina Gjurchevska Atanasovska, Solzica Popovska and Vladimir Cvetkoski (University of Niš, 2023)
In times of crisis, emergency education makes significant contributions to individuals and societies by providing a sense of normality (Johannes 2012). As teachers facilitate the learning process and are expected to support students emotionally, Muldong, Garcia & Gozum (2021) suggest that work-from-home teachers should be provided with psychosocial support to address the mental and emotional stress caused by the Covid-19 pandemic. El-Monshed, El-Adl, Ali and Loutfy (2021) and Carreon & Manansala (2021) suggest that educational institutions should also take measures to improve students’ mental health and academic performance and make it a priority in the current context. This paper reports the findings of a project on psychosocial support at Blaze Koneski Faculty in Skopje from March to June 2021 involving 15 language and translation teachers and 121 students. The teachers attended a series of workshops guided by a trained clinical psychologist. The workshops aimed at providing immediate psychosocial assistance to teachers to cope with the stress of the pandemic, to sensitise teachers to the students’ needs in an emerging crisis and to empower them to employ new ways of student engagement in the online classroom. The training concept was based on the assumption that one’s self-care and well-being are prerequisites for one to be able to care about others (in this context the students). The teachers tested various methods at two levels of classroom communication. They engaged in informal communication and introduced well-being techniques to create a relaxing class atmosphere and to facilitate the learning process. They also involved students in participative activities to help them take hold of their learning. Teacher and student feedback has been positive and points to the encouraging effect of this approach in the online environment and beyond it. It shows that the modern translation classroom, be it physical or virtual, requires giving students an active voice and a sense of control over their learning. It also shows that moving away from adhering to technical material to enrich the curriculum with topics and methods that address well-being and mental health is beneficial.
Keywords: emergency education, psychosocial support, well-being, teaching methods